Lucretia $1 (BVolume 05s - Lytton, Edward Bulwer Lytton, Baron, 1803-1873 (Salt Lake City, UT : Project Gutenberg, 2005)
"Lucretia $1 (BVolume 05" by Baron Edward Bulwer Lytton is a novel likely written in the mid-19th century. The story unfolds against a backdrop of intrigue and moral complexity, centering on several characters, including the opportunistic Nicholas Grabman, the devoted sweep Beck, and the enigmatic Lucretia, whose past and current actions weave through the fabric of the narrative. The book navigates themes of loyalty, betrayal, and the consequences of one's desires and ambitions. At the start of the novel, we see a glimpse into the lives of the main characters, particularly the troubled relationship between Grabman and Beck. Grabman's intentions appear dubious as he prepares to leave for the country, likely planning a secretive act against Beck, who has served him faithfully despite his unfortunate living conditions. The opening further sets the tone for the larger conflicts to emerge, highlighting the juxtaposition of human kindness and harshness, with Grabman's greed laid bare as he contemplates stealing from the impoverished Beck. This intricate initiation hints at deeper moral questions and relational dynamics that will unfold throughout the book. (This is an automatically generated summary.)s
Release date is 2005-03-01
This eBook was produced by Tapio Riikonen and David Widger
Keywords: London (England) -- Fiction; Detective and mystery stories, English; English fiction -- 19th century; Crime -- Fiction